Uncertainty, politics, and crises: The case for cash - Gerhard Rösl; Franz Seitz (Latin American Journal of Central Banking (LAJCB), 2024)
We analyze the repercussions of different kinds of uncertainty on cash demand, including uncertainty of cashless infrastructures, confidence crises of the financial system, natural disasters, political uncertainties, and inflationary crises. Based on a comprehensive literature survey and complemented by case studies, we derive a classification scheme how cash holdings typically evolved in each of these types of uncertainty over the past 30 years by separating between demand for domestic and international cash as well as between transaction and store of value balances. Hereby, we focus on the stabilizing macroeconomic properties of cash and recommend guidelines for cash supply by central banks and the banking system. Finally, we exemplify our analysis with five case studies from the developing world, namely Venezuela, Zimbabwe, Afghanistan, Iraq, and Libya.
Keywords: E41; E51; E58; O57; 330; Cash; Banknotes; Money; Crises; Stabilization; Uncertainty